A PROSPECTIVE STUDY ON BIPARIETAL DIAMETER AND FEMUR LENGTH UTILISING ULTRASONOGRAPHIC TECHNIQUES, ALONG WITH ITS CORRELATION TO FOETAL GESTATIONAL AGE. - Maharana, Sidharth Sankar; Ghanto, Shradha Suman (Student’s Journal of Health Research Africa, 2025)
Background The prenatal evaluation is crucial during pregnancy for evaluating the growth and development of the fetus. Ultrasonography is an accessible screening method for monitoring prenatal growth using fetal parameters and gestational age (GA). Femur length (FL) and biparietal diameter (BPD) are frequently utilized in the second trimester to evaluate fetal growth and ascertain precise gestational age. Studies indicated discrepancies in the reliability of FL and BPD for determining gestational age and fetal growth by ultrasonography. The purpose of the current study was to compare biparietal diameter and femur length with gestational age. Materials and Methods The study included 190 pregnant women in total. The participants ranged in age from 18 to 35 years, and their gestational ages ranged from 20 to 38 weeks. Results This investigation examined 79 cases in the second trimester, specifically between 20 and 27 weeks, and 110 instances in the 3rd trimester of pregnancy. The observed means of FL and BPD were 56.19 and 73.09, respectively. The standard error (SE) and the standard deviation (SD) of the mean for BPD and FL were 0.629, 0.569, and 12.79 and 11.59, respectively. Conclusion The study demonstrates a significant link between FL and BPD, with FL exhibiting good accuracy in assessing gestational age, while the correlation diminishes from 20 to 38 weeks. Recommendation Analyzing the growth patterns of FL and BPD by sonography will lead to better results.